2005
DOI: 10.1051/lait:2005004
|View full text |Cite
|
Sign up to set email alerts
|

Glycosyl hydrolases from Bifidobacterium adolescentis DSM20083. An overview

Abstract: -It is claimed that bifidobacteria have several health-promoting effects. To increase the amount of bifidobacteria in the colon the concept of probiotics and/or prebiotics can be applied. Bifidobacterium adolescentis is one of the main species of bifidobacteria in the gastro-intestinal tract of human adults. B. adolescentis is able to degrade a wide range of oligosaccharides and a number of glycosyl hydrolases have been characterized in detail. The hydrolytic activity of the glycosyl hydrolases from B. adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
(40 reference statements)
1
10
0
Order By: Relevance
“…Similar results were found for the heterologously produced enzyme [123,125,126]. In contrast to the preferred formation of 1 6 linkages during the transfer reaction, Leder et al [122] showed that 1 3 linkages are hydrolyzed at a higher rate than 1 6 linkages.…”
Section: A-galacto-oligosaccharides and Galactomannansupporting
confidence: 62%
See 1 more Smart Citation
“…Similar results were found for the heterologously produced enzyme [123,125,126]. In contrast to the preferred formation of 1 6 linkages during the transfer reaction, Leder et al [122] showed that 1 3 linkages are hydrolyzed at a higher rate than 1 6 linkages.…”
Section: A-galacto-oligosaccharides and Galactomannansupporting
confidence: 62%
“…In most cases, the for-mer is more predominant than the latter. For Bifidobacterium a-galactosidase we have found that, under the right conditions 69% of the cleaved galactose units are used in the transglycosylation reaction with melibiose as substrate [126]. Usually, the balance between hydrolysis and transglycosylation is much less favorable.…”
Section: Strategies For Efficient Prebiotic Oligosaccharide Productionmentioning
confidence: 99%
“…These enzymes are essential for bifidobacteria to be able to grow in milk or milk-components like lactose and lactose-derived transgalacto-oligosaccharides (TOS). Arabinofuranosyl-containing oligosaccharides derived from plant cell-wall constituents, such as arabinan and arabinoxylan, can be fermented by bifidobacteria through arabinoxylan- and arabinofurano-hydrolases [ 93 ]. However, the rate of degradation of these compounds is rather low and it has been assumed that other bacteria (e.g.…”
Section: Identification Of Existing and Novel Biochemical Routesmentioning
confidence: 99%
“…There are relatively few publications that review characterized carbohydrate hydrolases of Bifidobacterium sp. [141,142,145]. Therefore, this review will focus on the currently available knowledge on bifidobacterial carbohydrate metabolism, covering the utilization of monosaccharides, disaccharides, oligosaccharides and polysaccharides.…”
Section: Introductionmentioning
confidence: 99%